DNA vaccination against v-src oncogene-induced tumours in congenic chickens - Plachý, J V; Hejnar, J V; Trtková, K; Trejbalová, K; Svoboda, J; Hála, K (Vaccine, 2001)
DNA vaccination is particularly efficient for induction of cytotoxic T-lymphocyte (CTL) response. In our experiments, we used MHC(B) congenic chicken lines CB and CC (regressors and progressors of v-src-induced tumours, respectively) and a mutated, non-oncogenic v-src gene construct as the DNA vaccine. A high degree of vaccine protection against oncogenic v-src challenge was achieved in the CB line chickens. CTL response was demonstrated in vitro and by adoptive transfer of immune cells to the syngeneic host and to the CC line chickens rendered tolerant to CB cells. In the CC line chickens we observed tumour growth retardation after a low-dose DNA vaccination administered to immature recipients while higher amounts of DNA vaccine in immunocompetent chickens exerted an enhancing effect.
Keywords: kur domácí; onkogenní protein pp60(v-src); převzatá imunita; virová transformace buněk; geny src; Genes, src; Chickens; Sarcoma, Avian; Age Factors; Adoptive Transfer; viry ptačího sarkomu; Cell Transformation, Viral; Viral Vaccines; Avian Sarcoma Viruses; Oncogene Protein pp60(v-src); imunologická odpověď na dávku; Animals; kuřecí embryo; zvířata; věkové faktory; ptačí sarkom; Dose-Response Relationship, Immunologic; zvířata kongenní; DNA vakcíny; Vaccines, DNA; Animals, Congenic; virové vakcíny; Chick Embryo